Controlling the Electrical and Magnetoelectric Properties of Epitaxially Strained Sr1−xBaxMnO3 Thin Films. Issue 9 (24th February 2017) - Langenberg, Eric; Maurel, Laura; Marcano, Noelia; Guzmán, Roger; Štrichovanec, Pavel; Prokscha, Thomas; Magén, César; Algarabel, Pedro A.; Pardo, José A.
Abstract : The perovskite (Sr, Ba)MnO3 system is an ideal candidate for tailoring electrical and magnetoelectric properties through the accurate control of Ba content and epitaxial strain due to the strong coupling between polar instability, spin order, and lattice. Here, first, the polar order is proved to be induced in Sr1− x Ba x MnO3 thin films through lattice expansion either by epitaxial strain or chemical pressure, which correlates with the evolution of the dielectric properties. Second, due to strong spin–phonon coupling, a large magnetoelectric response is found in the (Sr, Ba)MnO3 system, in which the dielectric constant drops up to 50% when the antiferromagnetic order emerges, larger than most magnetoelectric oxides. More important, this coupling between magnetism and dielectric properties can be tuned from ≈18% to ≈50% by appropriately selecting Ba content and epitaxial strain. Third, a clear trend of increasing the band gap energy on increasing the unit cell volume either by epitaxial strain or chemical pressure is found, which opens the way for engineering the semiconducting properties of (Sr, Ba)MnO3 system at will. Thus, this work proves the possibility to design the electrical response and the magnetoelectric coupling in (Sr, Ba)MnO3 system. Abstract : Modifying the structure of perovskite (Sr, Ba)MnO3 at will through Ba content and epitaxial strain gives rise to an accurate control of electrical and magnetoelectric functionalities. It is revealed to be decisive to tip the balance between the polar and nonpolar ground state, to tune the strength of magnetoelectric coupling, and to design the semiconductor band gap energy.